(untitled) (Per Musi, 2014)
Due to the changes that characterize the history of art and theory of harmonic tonality, tonal plans that cover the so-called cycles of minor thirds (C:A:F#:Eb:C:) and cycles of major thirds (C:E:Ab:C:) have become an expansion and renovation solution that affected different genres and styles of music. By studying the use of these symmetrical plans in Brazilian songs from the second half of the twentieth century, this paper attempts to shed light on how such choices can have an impact on the valuation of works and artists in the field of popular music.